Bioaugmentation with PGP-trace element tolerant bacterial consortia affects Pb uptake by Helianthus annuus grown on trace element polluted military soils - Saran, A.; Imperato, V.; Fernandez, L.; Vannucchi, F.; Steffanie, N. M.; d'Haen, J.; Merini, L. J.; Vangronsveld, J.; Thijs, S. (International journal of phytoremediation, 2021)
In this study, we sought to compose consortia of plant growth-promoting (PGP) and trace element tolerant bacteria, to improve plant growth and inhibit uptake and translocation of trace elements, eventually allowing the cultivation of profitmaking crops on trace elements polluted soils, reducing the risks of entrance of these elements into the food chain. Sunflower (Helianthus annuus L.) was grown on two polluted military soils (MS1 and MS2) in greenhouse microcosms and inoculated with three different bacterial consortia (C1, C2, C3). Growth and physiological status of the plants were unaffected during the experiment with the inoculation. After 2 months, plants were harvested. Consortium C2 and C3 decreased Pb shoot bioaccumulation by respectively 80-85% when plants were grown in the MS1 and even to concentrations below detection limit in plants grown in MS2. Differences in uptake and (sub)cellular localization of Pb and Cd in selected bacterial isolates were investigated in vitro by TEM-EDX. Pb absorption was observed by Bacillus wiedmanni ST29 and Bacillus paramycoides ST9 cultures. While adsorption at the bacterial cell wall was observed by Bacillus paramycoides ST9 and retention in the extracellular matrix by Cellulosimicrobium cellulans ST54.